Communication, Collaboration and Commitment: Overcoming Conflict with Engaged Leadership - Charles P Gause (Academic Chairpersons Conference Proceedings, 2019)
Leadership is the ability to build and sustain high performance teams to achieve identified goals. Communication, Collaboration and Commitment are specific elements central to the survival and effectiveness of successful teams. This interactive presentation provides participants with a framework and solutions for being an engaging leader who resolves conflict.
Keywords: Collaboration Conflict Resolution Engaged Leadership